Effect of Turbulent-Flow Pasteurization on Survival of Mycobacterium avium subsp. paratuberculosis Added to Raw Milk - Pearce, Lindsay E. (American Society for Microbiology, 2001)
A pilot-scale pasteurizer operating under validated turbulent flow (Reynolds number, 11,050) was used to study the heat sensitivity of Mycobacterium avium subsp. paratuberculosis added to raw milk. The ATCC 19698 type strain, ATCC 43015 (Linda, human isolate), and three bovine isolates were heated in raw whole milk for 15 s at 63, 66, 69, and 72°C in duplicate trials. No strains survived at 72°C for 15 s; and only one strain survived at 69°C. Means of pooled D values (decimal reduction times) at 63 and 66°C were 15.0 ± 2.8 s (95% confidence interval) and 5.9 ± 0.7 s (95% confidence interval), respectively. The mean extrapolated D(72°C) was <2.03 s. This was equivalent to a >7 log(10) kill at 72°C for 15 s (95% confidence interval). The mean Z value (degrees required for the decimal reduction time to traverse one log cycle) was 8.6°C. These five strains showed similar survival whether recovery was on Herrold's egg yolk medium containing mycobactin or by a radiometric culture method (BACTEC). Milk was inoculated with fresh fecal material from a high-level fecal shedder with clinical Johne's disease. After heating at 72°C for 15 s, the minimum M. avium subsp. paratuberculosis kill was >4 log(10). Properly maintained and operated equipment should ensure the absence of viable M. avium subsp. paratuberculosis in retail milk and other pasteurized dairy products. An additional safeguard is the widespread commercial practice of pasteurizing 1.5 to 2° above 72°C.